A case report on Endoscopic Removal of Ingested Open Safety Pin (Nepal Medical College Journal, 2024)
Safety pin ingestion is a problem in gastrointestinal practice. Non - organic foreign bodies like needle, pin, coin and button are commonly ingested foreign bodies among the pediatric population. It may lead to severe morbidity and mortality. Most of the ingested foreign bodies are passed spontaneously without any endoscopic and surgical removal. Remaining foreign bodies can be retrieved and removed endoscopically or surgically.